1996
DOI: 10.1146/annurev.immunol.14.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxins: An Update

Abstract: The use of immunotoxins (ITs) in the therapy of cancer, graft-vs-host disease (GvHD), autoimmune diseases, and AIDS has been ongoing for the past two decades. ITs contain a targeting moiety for delivery and a toxic moiety for cytotoxicity. Theoretically, one molecule of a toxin, routed to the appropriate cellular compartment, will be lethal to a cell. Newly developed MoAbs, toxins, and molecular biological technologies have enabled researchers to construct ITs that can effectively kill many different cell type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
111
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(111 citation statements)
references
References 115 publications
0
111
0
Order By: Relevance
“…The response rates observed in phase I/II trials have often been higher than those reported for some of the conventional antiblastic drugs. 11,16,17 In this research, the cytotoxic effect of Rituximab conjugated to the RIP saporin-S6 has been studied for the first time. Moreover, we explored the possibility of combining immunotoxin and the chemotherapic drug Fludarabine, to augment the efficiency of killing target cells.…”
Section: Introductionmentioning
confidence: 99%
“…The response rates observed in phase I/II trials have often been higher than those reported for some of the conventional antiblastic drugs. 11,16,17 In this research, the cytotoxic effect of Rituximab conjugated to the RIP saporin-S6 has been studied for the first time. Moreover, we explored the possibility of combining immunotoxin and the chemotherapic drug Fludarabine, to augment the efficiency of killing target cells.…”
Section: Introductionmentioning
confidence: 99%
“…The separation process is an important step since it is necessary to avoid steric hindrance and allows an effective translocation of the toxin into the cytoplasm 25 . This can be accomplished by disulfide bonding 26 for the coupling of the toxin to a carrier molecule 9 .…”
Section: Introductionmentioning
confidence: 99%
“…IT therapy seems an excellent additional treatment in view of the potent and specific killing of malignant cells in vitro as well as in vivo. 1,2 ITs are constructed by linking chemically or genetically a cell binding moiety to a toxin. The commonly used toxins belong to the ribosome-inactivating proteins 3,4 and monoclonal antibodies (MoAbs) are usually used as targeting moiety.…”
Section: Introductionmentioning
confidence: 99%